Endocannabinoid Concentrations in Hair are Associated with PTSD Symptom Severity - Wilker, Sarah; Pfeiffer, Anett; Elbert, Thomas; Ovuga, Emilio; Karabatsiakis, Alexander; Krumbholz, Aniko; Thieme, Detlef; Schelling, Gustav; Kolassa, Iris-Tatjana (Psychoneuroendocrinology, 2016)
The endocannabinoid system has been implicated in the regulation of the stress response, fear memory formation, and inflammatory processes. Posttraumatic stress disorder (PTSD) can result from exposure to extreme stress and is characterized by strong, associative memories for the traumatic events experienced. Furthermore, an elevated physical disease risk has been observed in PTSD, likely to be mediated by inflammatory processes. Therefore, altered endocannabinoid regulation can be expected in individuals with PTSD. However, attempts to assess PTSD-associated differences in the endocannabinoid system from human blood samples have provided inconsistent results, possibly due to fluctuating levels of endocannabinoids. In hair, these neuromodulators are accumulated over time and thus give access to a more stable and reliable assessment. We therefore investigated PTSD-associated differences in hair concentrations of endocannabinoids (Nacyl- ethanolamides palmitoylethanolamide [PEA], oleoylethanolamide [OEA] and stearoylethanolamide [SEA]) in 38 rebel war survivors from Northern Uganda suffering from PTSD and N = 38 healthy rebel war survivors without current and lifetime PTSD. PTSD diagnosis and symptom severity were assessed in structured clinical interviews employing the Posttraumatic Diagnostic Scale (PDS). A significant group difference was observed for OEA, with PTSD patients showing reduced hair concentrations. Regression analyses further revealed strong negative relationships between all investigated N-acyl-ethanolamides and symptom severity of PTSD. The observed reductions in endocannabinoids might account for the increased inflammatory state as well as for the failure to extinguish fear memories observed in PTSD. Our findings add to the accumulating evidence suggesting the endocannabinoid system as a target for pharmacological enhancement of exposure-based psychotherapy for PTSD.
Keywords: Posttraumatic stress disorder; Endocannabinoids; Hair; Palmitoylethanolamide; Oleoylethanolamine; Stearoylethanolamine; Mass spectrometry